Model Simulasi Sebagai Alat Optimasi Produksi (Sebuah Studi Kasus) - Sultan Zubair Sultan (Teknik Mesin "TEKNOLOGI", 2009)
This paper presents the result of case study of the existing manufacturing system and discusses how simulation is used to improve the manufacturing system performances. In this paper, simulation was used as tools to evaluated utilization of the equipment. Based on simulation, if inter arrival time of raw material is 28 hours (4 days) with capacity 1500 unit, the equipments have queuing time as 3 hours. That time can be used as a periodically preventive maintenance in a production cycle. Keywords : Modelling and Simulation, Extend.